A protective film with enhanced edge peeling force for flexible OLED panel manufacturing process
By designing a protective film with edge peeling force enhancement characteristics in the manufacturing process of flexible OLED panels, the problem of dropping caused by insufficient peeling force of the existing protective film is solved, and a higher fitting effect and lower product scrapping rate is achieved.
Patent Information
- Application Number
- CN202411839932.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-13
AI Technical Summary
During the manufacturing process of flexible OLED panels, the peeling force of the existing protective film is insufficient, which causes the OLED panel and the protective film to fall off together during the flip process, resulting in product scrapping and economic losses.
A protective film with enhanced edge peeling force is designed, and the glue layer is divided into intermediate area and side area along the width direction. The peeling force of the side area is 1.5-3.5 times that of the middle area, ensuring that the edge peeling force is higher when flipped and preventing the phenomenon of sheet drop.
By increasing the edge peeling force of the protective film, the OLED panel and the protective film fall off together during the flip process is avoided, the risk of product scrapping is reduced, and the bonding effect between the protective film and the OLED panel is improved, and the occurrence of wrinkles is reduced.
Smart Images

Figure CN119307192B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of protective films, and in particular to an edge peeling force enhanced protective film for a flexible OLED panel manufacturing process. Background Art
[0002] A low-viscosity double-sided antistatic PET protective film is required in the manufacturing process of flexible OLED panels (PNL). Since the surface encapsulation coating of PNL is relatively fragile, the peeling force of the protective film needs to be controlled within 2g / 25mm to prevent damage to the coating when it is torn off in the later stage. During use, the protective film will be bonded to the glass and the surface encapsulation coating of PNL at the same time. The size relationship is glass substrate> protective film>PNL. The OLED panel is then separated from the glass substrate by laser separation, and the product is changed from rigid to flexible. Before bonding the lower support film, the glass substrate will be flipped over, and only a small part of the protective film on the edge will be bonded to the glass to support the PNL+protective film. If the peeling force of the protective film on the glass is low, it is easy for the PNL and the protective film to fall off from the glass surface as a whole (fall off) after flipping, resulting in product scrapping and causing great economic losses. Summary of the invention
[0003] In view of the above-mentioned shortcomings of the prior art, the present invention provides a protective film for a flexible OLED panel process, whose edge peeling force is greater than that in the middle area. While maintaining a small peeling force in the PNL bonding area, the peeling force in the glass bonding area is larger, and the film will not fall off.
[0004] Technical solution:
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0006] The present invention provides an edge peeling force enhanced protective film for a flexible OLED panel process, which comprises a substrate layer, an adhesive layer and a release film layer which are compositely connected in sequence from bottom to top, and the peeling force of the middle area of the adhesive layer is smaller than the peeling force of both sides.
[0007] Furthermore, the adhesive layer is divided into three regions along the width direction, namely the middle region B and the side regions A and C arranged on both sides of the middle region B, and the peeling force of the side regions A and C is 1.5-3.5 times that of the middle region B. In the present technical solution, the effect is not good if it is less than 1.5 times, and it is difficult to tear off the rear end if it is more than 3.5 times.
[0008] Preferably, the peeling force of the side region A and the side region C is 2-3 times the peeling force of the middle region B.
[0009] Most preferably, the peeling force of the side region A and the side region C is 2.5-3 times that of the middle region B. Specifically, the peeling force of the side region A and the side region C is 2.5, 2.6, 2.7, 2.8, 2.9, 3.0 times that of the middle region B, and a range between any two of the foregoing values.
[0010] Furthermore, the peeling force of the side region A and the side region C is 2-6 gf / 25mm. If the peeling force is too high, it is difficult to tear off the back end; if the peeling force is too low, the effect of improving the film falling off and the laminating wrinkles is not obvious.
[0011] Preferably, the peeling force of the side region A and the side region C is 2.0-4.0 gf / 25mm;
[0012] Most preferably, the peeling force of the side region A and the side region C is 2.5-3.5 g / 25 mm. Specifically, the peeling force of the side region A and the side region C is 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5 g / 25 mm and a range between any two of the foregoing values.
[0013] Furthermore, the peeling force of the middle region B is 0.5-2.0 gf / 25mm. If it exceeds 2.0, the PNL packaging coating is easily damaged, and if it is less than 0.5g / 25mm, the laminated PNL is easy to fall off.
[0014] Preferably, the peeling force of the middle region B is 0.8-1.2 g / 25mm. Specifically, the peeling force of the middle region B can be 0.8 g / 25mm, 0.9 g / 25mm, 1.0 g / 25mm, 1.1 g / 25mm, 1.2 g / 25mm, or a range between any two of the foregoing values.
[0015] Furthermore, the width of the side area A and the side area C is 5-30 mm; the width of the middle area B is 850 mm-1400 mm.
[0016] Furthermore, the side regions A and C are symmetrically distributed on both sides of the middle region B.
[0017] Furthermore, the substrate layer is an antistatic PET base film, and the thickness of the substrate layer is 50-100um; the light transmittance is greater than 85%, and the haze is less than 3%.
[0018] Furthermore, the adhesive layer is antistatic polyurethane PSA, and the thickness of the adhesive layer is 50-100 um.
[0019] Preferably, the antistatic polyurethane PSA adopts the solvent-free antistatic polyurethane PSA disclosed in patent ZL202211442399.X; specifically, the solvent-free antistatic polyurethane PSA components are composed of 40-70 parts of polyurethane acrylate, 20-70 parts of active diluent, 1-5 parts of photoinitiator and 0.5-3 parts of antistatic agent by weight; the above components are mixed at room temperature, stirred at a high speed of 800-2500r / min, and used after filtering with a filter element; the polyurethane acrylate is a polyether polyurethane acrylate with a molecular weight of 2000-20000, a functional group of 2, and a glass transition temperature of -60°C to -20°C; the active diluent adopts an acrylate active diluent.
[0020] Most preferably, the solvent-free antistatic polyurethane PSA is prepared by the preparation method in Example 1 of Patent ZL202211442399.X, specifically as follows: a difunctional polyether polyurethane acrylate with a molecular weight of 4000 and a glass transition temperature of -40°C, ethoxylated ethyl acrylate, caprolactone acrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, 184, TPO-L, and LiTFSI are mixed in a weight ratio of 50:20:20:10:6:1:1:0.2, stirred at a speed of 800 rpm for 40 minutes, filtered with a 10um filter element, and placed for use after vacuum degassing.
[0021] Furthermore, the release film is a double-sided antistatic PET release film, and the thickness of the release film is 25-100um; preferably 25um / 50um, the release film is also double-sided antistatic, the substrate surface impedance value is 1*10^4-1*10^7Ω, and the release film surface impedance value is 1.0*10^5-1*10^8Ω.
[0022] A method for preparing a protective film with enhanced edge peeling force, comprising coating an antistatic PSA on an antistatic PET surface, laminating a PET release film and curing the film with a UV lamp, performing LED energy gradient zoning in a width region to be divided into ABC regions, wherein the A region and the C region are symmetrically designed, and the energy of the A / C region is controlled to be 1 / 3-1 / 10 of that of the B region.
[0023] Specifically, the energy range of area B is controlled to be 2000-5000 mj / cm 2 .
[0024] The energy range of AC area is 50-300mj / cm 2 .
[0025] The invention discloses an edge peeling force enhanced protective film which can be applied to the protection of flexible OLED panel manufacturing process.
[0026] When in use, remove the release film, and use the base material + glue as a whole layer to adhere to the glass substrate and the flexible OLED panel (the OLED panel is evaporated on the glass substrate, which is about 13mm larger than the glass substrate. The protective film is smaller than the glass and larger than the OLED panel. The middle area adheres to the OLED panel and the edge adheres to the glass. The width of the adhesion to the edge of the glass is about 11mm).
[0027] Beneficial effects:
[0028] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:
[0029] (1) The present invention coats the antistatic PSA between the antistatic PET substrate and the double-sided antistatic release film by a double-roll coating method, and passes through a UV light box with an energy gradient, wherein the energy in the middle region is 3 to 10 times that of the edge region. After curing, an edge peeling force-enhanced protective film with low peeling force in the middle region and high peeling force at the edge is obtained. The edge peeling force of the prepared protective film is 1.5-3.5 times that of the middle region. The protective film is used as a protective film for the process of flexible OLED panels (PNL). After the PNL is separated from the glass substrate by laser, it will not fall off when it is turned over and left to stand. At the same time, the bonding effect between the protective film and the waste material area at the edge of the PNL is improved, and the occurrence of wrinkles is reduced.
[0030] (2) The peeling force in the middle and edge regions of the prior art is consistent. When the peeling force is too high, the coating is easily torn when the protective film is torn off at the back end, resulting in poor functionality and product scrapping. When the peeling force is too low, the glass is easily flipped and the pieces fall off, causing damage to the product and scrapping. Compared with the prior art, the peeling force at the ends and the middle region of the product made by the present invention is different. The edge peeling force is higher, and the laminated glass is not easy to fall off when flipped. The glass in the middle region is small, and the coating will not be torn off when the back end is torn off together. At the same time, the edge bonding effect is improved and the occurrence of wrinkles is reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 It is a schematic structural diagram of a protective film for enhancing edge peeling force for a flexible OLED panel manufacturing process according to the present invention;
[0033] Figure 2 This is a schematic diagram of regional distribution;
[0034] Figure 3This is a schematic diagram of the protective film lamination;
[0035] Figure 4 Schematic diagram of LED energy gradient partitioning for width areas.
[0036] 1-substrate layer, 2-adhesive layer, 3-release film layer, 4-middle area B, 5-side area A, 6-side area C, 7-edge waste area, 8-glass substrate, 9-PNL area, 10-protective film. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The present invention will be further described below in conjunction with the embodiments.
[0039] (I) Implementation examples:
[0040] Embodiment 1:
[0041] A protective film with enhanced edge peeling force for a flexible OLED panel process, comprising a substrate layer, an adhesive layer and a release film layer which are compositely connected in sequence from bottom to top; the substrate layer is an antistatic PET base film, and the thickness of the substrate layer is 75um, and the back side impedance value is 10^5Ω; the release film is a double-sided antistatic PET release film, and the thickness of the release film is 50um, the back side impedance value is 10^5Ω, and the release surface impedance value is 10^5Ω; the adhesive layer is a solvent-free antistatic polyurethane PSA, and the thickness of the adhesive layer is 75um, and the adhesive surface impedance value is 10^9Ω.
[0042] The adhesive layer is divided into three regions along the width direction, namely the middle region B and the side regions A and C symmetrically arranged on both sides of the middle region B. The width of the middle region B is 875 mm, and the peeling force of the middle region B is 1.2 gf / 25 mm; the widths of the side regions A and C are both 20 mm, and the peeling forces of the side regions A and C are 3.2 gf / 25 mm.
[0043] Among them, the solvent-free antistatic polyurethane PSA is prepared by the preparation method in Example 1 of Patent ZL202211442399.X, specifically as follows: a bifunctional polyether polyurethane acrylate with a molecular weight of 4000 and a glass transition temperature of -40°C, ethoxylated ethyl acrylate, caprolactone acrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, 184, TPO-L, and LiTFSI are mixed in a weight ratio of 50:20:20:10:6:1:1:0.2, stirred at a speed of 800 rpm for 40 min, filtered with a 10um filter element, and vacuum degassed for standby use;
[0044] The protective film preparation method is as follows: the prepared solvent-free antistatic polyurethane PSA is coated on the antistatic PET surface of the substrate layer by a double-roll coating method, and after the PET release film is attached, the middle area B and the two side areas AC are respectively cured by UV-LED with different energies to obtain the protective film.
[0045] Comparative Examples 1-5:
[0046] The only difference from Example 1 is that the peeling forces of the middle area and the two side areas are different, as shown in Table 1 below.
[0047] Comparative Example 6:
[0048] The only difference from Example 1 is:
[0049] The peeling force of the middle area and the two side areas is different, as shown in Table 1 below;
[0050] At the same time, the adhesive layers used are different. Among them, the preparation method of the ordinary pressure-sensitive adhesive in Comparative Example 6 is as follows: by weight, 40 parts of polyester polyurethane acrylate with a functionality of 2, a molecular weight of 5000, and a glass transition temperature of -40°C, 30 parts of octyl acrylate, 25 parts of ethoxylated ethyl acrylate, 5 parts of trimethylolpropane triacrylate, 2 parts of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 0.5 parts of lithium perchlorate are mixed and stirred to uniformly prepare a pressure-sensitive adhesive.
[0051] Comparative Example 7:
[0052] The only difference from Example 1 is that the peeling forces of the middle area and the two side areas are different, as shown in Table 1 below; the substrate layer uses a PET base film that has not been treated with antistatic treatment.
[0053] Comparative Examples 8-9:
[0054] The only difference from Example 1 is that the peeling forces of the middle area and the two side areas are different, as shown in Table 1 below.
[0055]
[0056] Note: Except for the numerical values in the table, the other aspects of Comparative Examples 1-9 are the same as those of Example 1.
[0057] The time it takes for the product to fall off after the glass is flipped and left to stand: remove the release film, and adhere the base material + adhesive as a whole layer to the glass substrate and the flexible OLED panel. Then separate the OLED panel from the glass substrate by laser separation. The product changes from rigid to flexible. Flip the glass substrate and measure the time it takes for the product to fall off after the glass is flipped and left to stand.
[0058] Back-end tearing test: Roll up the film with a roller, clamp it and tear it off automatically. There is a certain speed when tearing it off, generally 20-60mm / s.
[0059] Film tearing voltage: By moving a 2kg hand roller back and forth three times, the surface protective film (width 50mm×length 150mm) with the release film peeled off is attached to the glass plate. Under the environmental conditions of 23±2℃ and 50±5%RH, the cursor of the static tester (KEYENCE SK-H050) is aligned with the test surface, and the start key is pressed to clear the test surface. The protective film is peeled off at a speed of 15m / min. The absolute value of the static meter value obtained is the static electricity.
[0060] Success rate of release film tearing: Place the protective film on the vacuum platform, roll up a corner of the release film with a high-viscosity rubber roller, grab the release film with the clamp, and peel it off at a speed of 20m / min. When the release film is torn off, observe whether the PET substrate is not separated from the vacuum platform and the release film does not fall off from the clamp position, which is considered to be a successful film tearing.
[0061] Edge lamination wrinkle incidence rate: The protective film is laminated to the PNL surface with a glass substrate. The edge of each substrate is divided into 50 areas. The number of edge wrinkles is visually counted and divided by the total number to obtain the lamination wrinkle incidence rate.
[0062]
[0063] It can be seen from the above embodiments and comparative examples that the peeling force of the middle area B of the adhesive layer should be controlled in the range of 0.5-2.0g / 25mm, and the peeling force of the side area AC of the adhesive layer should be controlled in the range of 2-6 gf / 25mm. When the peeling force of the side area AC is 1.5-3.5 times that of the middle area B, various performances such as static peeling time, film tearing voltage, rear-end tearing test, release film tearing success rate, and bonding bubbles can be optimized.
[0064] In the present invention, the peeling force of the middle area of the adhesive layer should be controlled in the range of 0.5-2.0g / 25mm, otherwise it is easy to cause the PNL surface coating to be torn off at the rear end and damaged; the peeling force of the AC area is 2-6g / 25mm, if the peeling force is too high, it is difficult to tear off at the rear end, and if the peeling force is too low, the effect of improving the film falling and the lamination wrinkles is not obvious; in addition, the peeling force of the side area A and the side area C is 1.5-3.5 times that of the middle area B. If it is lower than 1.5 times, the effect is not good, and if it is higher than 3 times, it is difficult to tear off at the rear end.
[0065] The peeling force in the middle and edge areas of the prior art is consistent. When the peeling force is too high, the coating is easily torn when the protective film is torn off at the back end, resulting in poor functionality and product scrapping. When the peeling force is too low, the glass is easily flipped and the pieces fall off, resulting in product damage and scrapping. Compared with the prior art, the peeling force at the two ends and the middle area of the product made by the present invention is different. The edge peeling force is higher, and the laminated glass is not easy to fall off when flipped. The glass in the middle area is small, and the coating will not be torn when the back end is torn off together. At the same time, the edge bonding effect is improved and the occurrence of wrinkles is reduced.
[0066] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.
Claims
1. A protective film with enhanced edge peeling force for a flexible OLED panel manufacturing process, characterized in that: It comprises a substrate layer, an adhesive layer and a release film layer which are compositely connected in sequence from bottom to top, and the peeling force of the middle area of the adhesive layer is smaller than the peeling force of the two sides; The adhesive layer is divided into three regions along the width direction, namely, a middle region B and side regions A and C arranged on both sides of the middle region B, wherein the peeling force of the side regions A and C is 1.5-3.5 times that of the middle region B; The peeling force of the middle region B is 0.5-2.0 gf / 25mm.
2. The edge peeling strength enhancing protective film for flexible OLED panel manufacturing process according to claim 1, characterized in that: The peeling force of the side area A and the side area C is 2-6 gf / 25mm.
3. The edge peeling strength enhancing protective film for flexible OLED panel manufacturing process according to claim 1, characterized in that: The width of the side area A and the side area C is 5-30 mm; the width of the middle area B is 850 mm-1400 mm.
4. The edge peeling strength enhancing protective film for flexible OLED panel manufacturing process according to claim 1, characterized in that: The side regions A and C are symmetrically distributed on both sides of the middle region B.
5. The edge peeling strength enhancing protective film for flexible OLED panel manufacturing process according to claim 1, characterized in that: The substrate layer is an antistatic PET base film, and the thickness of the substrate layer is 50-100um; the light transmittance is greater than 85%, and the haze is less than 3%.
6. The edge peeling strength enhancing protective film for flexible OLED panel manufacturing process according to claim 1, characterized in that: The adhesive layer is antistatic polyurethane PSA, and the thickness of the adhesive layer is 50-100um; The release film is a double-sided antistatic PET release film, and the thickness of the release film is 25-100um.
7. A method for preparing a protective film for enhancing edge peeling force for a flexible OLED panel manufacturing process according to any one of claims 1 to 6, characterized in that: The antistatic PSA is coated on the antistatic PET surface, and the PET release film is attached and cured by UV lamp. The LED energy gradient is divided into ABC areas in the width area. The A and C areas are symmetrically designed, and the energy of the A / C area is controlled to be 1 / 3-1 / 10 of the B area.
8. An edge peeling force enhanced protective film for a flexible OLED panel process as described in any one of claims 1 to 6, and an edge peeling force enhanced protective film prepared by the preparation method described in claim 7, which are used for flexible OLED panel process protection.
Citation Information
Patent Citations
PET (Polyethylene Terephthalate) protection film for cover plate glass manufacturing procedure or delivery process and preparation method thereof
CN108864977A
OLED (Organic Light Emitting Diode) manufacturing process protective film and preparation method thereof
CN115491145A